2020
DOI: 10.2140/agt.2020.20.531
|View full text |Cite
|
Sign up to set email alerts
|

On spectral sequences from Khovanov homology

Abstract: There are a number of homological knot invariants, each satisfying an unoriented skein exact sequence, which can be realized as the limit page of a spectral sequence starting at a version of the Khovanov chain complex. Compositions of elementary 1-handle movie moves induce a morphism of spectral sequences. These morphisms remain unexploited in the literature, perhaps because there is still an open question concerning the naturality of maps induced by general movies.In this paper we focus on the spectral sequen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…in Theorem 1.3. The third author and Zentner [26] recently used the idea that diagrammatic 1-handle additions induce morphisms of spectral sequences to compute the singular instanton and Heegaard Floer spectral sequences for a variety of knots, even without the assumption (proved in this paper) that the morphism associated to a movie for a cobordism is independent of the movie. The functoriality established here should allow us to extend these sorts of calculations to a wider array of knots.…”
Section: Introductionmentioning
confidence: 99%
“…in Theorem 1.3. The third author and Zentner [26] recently used the idea that diagrammatic 1-handle additions induce morphisms of spectral sequences to compute the singular instanton and Heegaard Floer spectral sequences for a variety of knots, even without the assumption (proved in this paper) that the morphism associated to a movie for a cobordism is independent of the movie. The functoriality established here should allow us to extend these sorts of calculations to a wider array of knots.…”
Section: Introductionmentioning
confidence: 99%
“…As explained in [18, Proposition 3.1] (see Proposition 6.1 above), any representation of a, b, c, d | ba = cd taking a, b, c, d to traceless elements is conjugate to one given by (25) a We have shown that to each (γ, θ) ∈ P there exists a unique ρ ∈ R δ (S 2 × I, {a, b, c, d} × I), given by (25), (26), and (27). Moreover the restriction…”
Section: Perturbing Near the 2-spherementioning
confidence: 96%
“…Figure 16 shows the 4-punctured 2-sphere with the four based meridian generators a, b, c, d based at a point s. An additional curve e is also indicated. We have shown that to each (γ, θ) ∈ P there exists a unique ρ ∈ R δ (S 2 × I, {a, b, c, d} × I), given by ( 25), (26), and (27). Moreover the restriction…”
Section: Examples: 2-bridge Knotsmentioning
confidence: 99%
See 1 more Smart Citation
“…For a link homology theory pCpLq, d L q, it is natural for the deformation ǫ :" ǫ L to depend on the link L in such a manner that the chain complex pCpLq, d L `ǫL q remains invariant under the Reidemeister moves. Such constructions give rise to spectral sequences (see [10], [1], [7], [8]). Since there are many deformations of Khovanov homology, one can ask whether there are relations among them.…”
Section: Introductionmentioning
confidence: 99%